Short‐term and long‐term positive outcomes of the multidisciplinary care implemented by the French health networks for the prevention and care of paediatric overweight and obesity. Issue 8 (16th April 2019) - Carriere, Caroline; Thibault, Hélène; Barat, Pascal; Guemazi‐Kheffi, Fatiha; Mellouet‐Fort, Blandine; Ancillon, Laurent; Bertrand, Anne‐Marie; Quinart, Sylvain; Guilmin‐Crépon, Sophie; Arsan, Armine; Lestournelle, Anne; Brument, Régine; et al.
Summary: Background: The nine French regional health networks for the prevention and care of paediatric obesity offer a 2‐year program of multidisciplinary primary care (medical, dietetical, psychological, adapted physical activity) based on multicomponent lifestyle interventions. Objectives: To assess the short‐term and long‐term impact of care management. Methods: The impact of the multidisciplinary care was assessed by changes in the body mass index (BMI) Z score during the period of the care, and at least 2 years after the end. Anthropometric data were collected at baseline and at the end of the care either through a digital medical file or through direct phone contacts with the referring. Long‐term outcomes were assessed through studies relative to post follow‐up evaluation. Results: At the end of the period of the care in a network, 72.9% of 6947 children had decreased their BMI Z score from 3.6 ± 1.0 DS at baseline to 3.3 ± 1.1 DS at the end. The four studies relative to long‐term evaluation showed a pursuit of the decrease of BMI Z score during the 5.1 years after the beginning of the care. Conclusions: The care provided by regional French networks for prevention and care of paediatric obesity induce a reduction of BMI that continues afterwards.